The Influence of Think Pair Share Strategy Towards Students’ Writing Ability of Recount Text - Badriyatus Sholihah; Ria Kamilah Agustina (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to obtain empirical evidence about the influence of using Think Pair Share technique on students’ writing of recount text at tenth grade of SMPN 1 Gudo in the Academic Year 2021/2022. This study uses quantitative methods and the research design used is a quasi-experimental design. The populations of this study were all students of class VIII. The sampling technique used was purposive sampling consisting of 64 students. The sample was divided into two groups, namely class VIII D as the experimental class and class VIII H as the control class. Each class consists of 32 students. The instrument used is a written test. This research procedure begins with conducting a preliminary study, identification of research problems, development of research instruments, validation of research instrument, data collection, data analysis and communication of results. The result obtained from data quantification using t test with a significance level (a) = 0.05. the results showed that the average post-test score in the experimental class was higher than in the control class (75.15 > 74.06). then, the statistical hypothesis test showed that the post-test value was 0.039 < sig. one = 0.05. this means that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. In conclusion, the Think Pair Share technique affects the writing of recount text by students.